Pemahaman Realisasi Hadits Tentang Zihar Dalam Rumah Tangga - Suryani Suryani (UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: Zihar in marriage is a practice carried out by the husband by making statements that equate his wife with members of his family which does not allow for a husband-wife relationship. In the practice of zihar, the husband is not permitted to interfere or do things related to his wife that are forbidden. The practice of zihar has a background in the Arab Jahiliyah tradition, where husbands use zihar as an effort to restrain or avoid relations with their wives. In the context of Islamic law, zihar is considered a violation and requires payment of a fine or kafarat so that the statement of zihar does not have the effect of divorce (talaq). In the course of history, the concept of zihar has experienced development and interpretation from various schools of thought in Islam. There are differences of opinion regarding whether a statement is categorized as zihar based on the part of the body depicted or the meaning contained therein. Although zihar is a practice that occurred in the past, it is important for people to understand this concept well. Scientific study and in-depth understanding of zihar can help resolve conflicts in marriage, maintain justice and women's rights, and implement Islamic values which prioritize love, mutual understanding and unity in husband-wife relationships.Keywords: Realization, Understanding, Zihar, Household Abtsrak : Zihar dalam pernikahan merupakan sebuah praktik yang dilakukan oleh suami dengan mengucapkan pernyataan yang menyamakan istrinya dengan anggota keluarganya yang tidak memungkinkan adanya hubungan suami-istri. Dalam praktik zihar, suami tidak diizinkan untuk mencampuri atau melakukan hal-hal terkait dengan istri yang telah diharamkan. Praktik zihar tersebut memiliki latar belakang dalam tradisi Jahiliyah Arab, di mana suami menggunakan zihar sebagai upaya untuk menahan atau menghindari hubungan dengan istrinya. Dalam konteks hukum Islam, zihar dianggap sebagai pelanggaran dan memerlukan pembayaran denda atau kafarat agar pernyataan zihar tersebut tidak berdampak sebagai perceraian (talaq). Dalam perjalanan sejarah, konsep zihar mengalami perkembangan dan penafsiran dari berbagai mazhab dalam Islam. Terdapat perbedaan pendapat mengenai apakah suatu pernyataan dikategorikan sebagai zihar berdasarkan anggota tubuh yang diperumpamakan atau maksud yang terkandung di dalamnya. Meskipun zihar merupakan praktik yang terjadi pada masa lalu, penting bagi masyarakat untuk memahami konsep ini dengan baik. Kajian ilmiah dan pemahaman yang mendalam tentang zihar dapat membantu dalam menyelesaikan konflik dalam pernikahan, menjaga keadilan dan hak-hak perempuan, serta mengimplementasikan nilai-nilai Islam yang mengedepankan kasih sayang, saling pengertian, dan kesatuan dalam hubungan suami-istri.Kata kunci : Realisasi, Pemahaman, Zihar, Rumah Tangga